The impact of experimental fires on mesofauna communities (Collembola and Acarina) of two kinds of meadows - Olejniczka, Izabella; Russel, Stefan; Prędecka, Anna (Studia Ecologiae et Bioethicae, 2011)
The impact of experimental fires in grasslands on soil mesofauna was studied in the field experiment. The study was carried out on two kinds of meadows: on mineral (meadow I) and organic soils (meadow II), near Warsaw (52010’N; 20050’E). In November 2007 sampling plots, 1 m2 in size were chosen at random and burnt. Soil samples were taken just after fire and in April, July, and November 2008 to the depth of 10 cm from unburned places (control), at the border of fire and in burnt plots. The soil mesofauna was extracted from soil samples in the Tullgren apparatus. There were not found any effects of experimental fires on mesofauna densities. However, a slight increase of mesofauna abundance was s observed in burned plots 12 months after experimental fires on the meadow I and decrease on the meadow II. Just after fire, in burned plots, only euedaphic species of Collembola were present among mites communities dominated Oribatida, with thick cuticule.